Recognition of Gallotannins and the Physiological Activities: From Chemical View - He, Hua-Feng (Frontiers in Nutrition, 2022)
Gallotannins, characterized with the glycosidic core and galloyl unit, are seemed as vital components of hydrolysable tannins. Benefit from the more and more discoveries of their bio-activities and edibility, application of gallotannins in food industry, pharmacy industry and other fields is increasing. Inheriting previous research achievements, chemical structure of gallotannins was illustrated, degradation as well as synthetic routes to gallotannins was summarized. On this basis, distribution in the nature also including the distinction of gallotannins was discussed. More than that, activities involving in antioxidant, anti-inflammatory, enzyme inhibitions, protein-binding and so on, as well as applications in the field of food industry, bio-pharmaceutical science, agricultural production, etc. were combed. Finally, improvement of bioavailability, chemical modification of the structure and accurate determination of new gallotannins were pointed out to be the orientation in the future.